THE DECISION SUPPORT SYSTEM IN SELECTING THE OUTSTANDING STUDENTS AT SMKN 1 TULANG BAWANG USING ANALYTICAL HIERARCHY PROCESS - Darsin, Darsin; PRAYOGA, DANIEL (International Journal of Ethno-Sciences and Education Research, 2022)
In the era of globalization, many information technology developments in the field of education began to develop administrative systems using information technology, one of which is by using web-based applications.Decision Support system for the selection of the outstanding students In SMKN 1 Tulang Bawang Using Analytical Hierarchy Process Method the system processes the calculation and disbursement of student achievement data with PHP programming language and Php MyAdmin as a tool to help manage databases using XAMPP.The Decision Support System for The Selection of Outstanding Students can provide convenience for the school in monitoring students and students can also obtain all information on facilities and news in the school.